Modernism, God, and Church in the Thinking of J. Macbride Sterrrett - Ciprian, Simuț (European Journal of Multidisciplinary Studies, 2016)
Modernism was a movement that impacted the church. In spite of the fact that many modernists wrote against the church, there were some, such as J. Macbride Sterrett, who not only defended the church, but also integrated modernist principles into their perspectives on what the church should be. Sterrett was also a clergyman in the Protestant Episcopal Church, which offered a deeper meaning to his modernist thought. This paper presents the main ideas in relation to history, church and society. His perspectives defend the identity of the church and its use in modern society. Sterrett’s ideas are useful also because they present a purpose for the church, that is quite easy to understand for the secular environment.
Keywords: Modernism, God, and Church in the Thinking of J. Macbride Sterrrett